(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In this study, the theorem on necessary and suï¬ƒcient conditions for the solvability of inverse problem for Sturm-Liouville operator with discontinuous coeï¬ƒcient is proved and the algorithm of reconstruction of potential from spectral data (eigenvalues and normalizing numbers) is given.